Foot orthoses improve kinematic measurement in young women with biomechanical abnormality - Maria Regina Rachmawati; Angela BM Tulaar; Muctarudin Mansyur; Ferial Hadipoetro Idris; Ismail Ismail; Ratna Darjanti Haryadi (Faculty of Medicine, Universitas Trisakti, 2013)
BACKGROUNDFoot pronation causes biomechanical abnormalities in the form of functional leg-length disparity. Foot orthoses are often used in the treatment of abnormal pronation. The aim of the study was to evaluate the effect of foot orthoses on abnormal kinematic chain the differences of pelvic height, step length, and walking distance on walking test in young women with biomechanical abnormality.METHODS A randomized double blind controlled clinical trial was conducted on 27 young adult women having abnormal biomechanical abnormalities. By random allocation the subjects were divided into the intervention group (14 subjects) receiving correction of foot pronation using foot orthoses, and the control group (13 subjects) receiving no orthoses. Before and during use of foot orthoses, we determined pelvic height difference (mm), step length difference (cm), and walking distance at maximal walking speed for 15 minutes. RESULTS Correction of foot pronation resulted in decreased pelvic height difference from 4.7 ± 2.1 mm to 1.7 ± 1.3 mm (p<0.001) and in a reduction in step length difference, from 4.9 ± 2.9 cm to 2.1 ± 1.5 cm (p=0.002). Walking test distance of the intervention group was 1318.5 ± 46.3 m, as compared with that of the control group of 1233 ± 114.7 m (p = 0.05). Walking distance of the intervention group rose steadily in the second test to 1369.3 ± 27 m, and in the third test to 1382.14 ± 10.5 m (p<0.001). CONCLUSIONS Foot orthoses improved the kinematic chain, resulting in a more symmetrical pelvic height, reduced step length difference, and increased functional walking ability.